2007
DOI: 10.1111/j.1365-2923.2007.02785.x
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a new doctor: a learning or survival exercise?

Abstract: Without the support of senior colleagues who can help the new doctor reflect on quite difficult and uncertain situations, new doctors will almost certainly perceive the first year of the new Foundation Programme as a survival exercise. If new doctors are working in an environment where their learning is properly facilitated, they are more likely to recognise their progress in their professional development and be more proactive in addressing concerns about professional expectations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 8 publications
2
49
0
Order By: Relevance
“…However, as other investigators have also found [3], they reported feeling under-prepared for management and administrative skills, and medical educators should consider explicitly discussing the more technical aspects of the intern role to prepare students for the fact that administrative tasks form a large part of their working day. Although active participation in their hospital communities of practice, and especially junior doctor shadowing, have previously been identified as particularly valuable for intern preparation [1, 2], participants reported having felt pressured to spend time with more senior clinicians instead. They were very aware of the potential negative impact on their careers of poor relationships with senior doctors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, as other investigators have also found [3], they reported feeling under-prepared for management and administrative skills, and medical educators should consider explicitly discussing the more technical aspects of the intern role to prepare students for the fact that administrative tasks form a large part of their working day. Although active participation in their hospital communities of practice, and especially junior doctor shadowing, have previously been identified as particularly valuable for intern preparation [1, 2], participants reported having felt pressured to spend time with more senior clinicians instead. They were very aware of the potential negative impact on their careers of poor relationships with senior doctors.…”
Section: Discussionmentioning
confidence: 99%
“…Team support has also been recognised as critical in previous literature, particularly teams which show interest in the junior doctor as an individual [3] and provide regular feedback [1]. Shadowing junior doctors and sharing experiences with peers have also previously been identified as particularly valuable [12, 17]; this sharing may promote the “strong sense of shared social identity” which is known to be a factor in buffering stress [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations